(untitled) (Bangladesh Journal of Zoology, 2015)
Experiment was conducted to assess the potential of increasing production of shrimp, Penaeus monodon by enhancing primary production through fertilization and reduc feeding regime. Four treatments viz., T1, feeding @ 2% of shrimp biomass from 31 80 days of culture and then 1%; T2, feeding @ 3% of shrimp biomass from 31 80 days of culture and then 2%; T3, feeding @ 2% of shrimp biomass from 31 80 days of culture and then 1% + fertilization; T4, feeding @ 3% of shrimp biomass from 31 80 days of culture and then 2% + fertilization each with three replications were tested. Urea @1.25 ppm and TSP @ 1.50 ppm were applied as fertilizer monthly. After 120 days of culture, mean final weight of shrimp was 11.86±0.35g, 12.08±0.51g, 13.30±0.99g and 14.50±1.14g with the production of 458.36±14.86 kg/ha, 484.93±7.26kg/ha, 536.75±4.81 kg/ha and 592.19±35.05 kg/ha in T1, T2, T3 and T4, respectively. Reduction of feed reduce both growth and production of shrimp. Increase in primary productivity due to fertilization increase production of shrimp to a significant level (F=32.94; p<0.001). But overall production of shrimp was lower in comparison to other similar studies when higher feeding applied. Bangladesh J. Zool. 43(1): 9-17, 2015